2018
DOI: 10.1186/s12883-018-1065-9
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional and longitudinal study evaluating brain volumes, RNFL, and cognitive functions in MS patients and healthy controls

Abstract: BackgroundThe principal biomarker of neurodegeneration in multiple sclerosis (MS) is believed to be brain volume, which is associated with cognitive functions and retinal nerve fibre layer (RNFL). A cross-sectional and longitudinal assessment of the relationship between RNFL, cognitive functions and brain volume.MethodsAt baseline, relapsing patients and healthy controls underwent 1.5 T MRI to estimate the normalized volume of brain (NBV), grey (NGV), white (NWV) and peripheral grey (pNGV) matter. Cognitive fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 27 publications
(37 reference statements)
3
22
0
Order By: Relevance
“… 31 34 We have previously reported a lower RNFL thickness in patients with RRMS with and without a history of ON that was related to EDSS and MSSS. 28 Furthermore, a progressive thinning of RNFL has been shown in longitudinal studies of patients with MS, 35 37 and a recent longitudinal study of 57 patients with MS reported progressive RNFL thinning over 5 years, regardless of a history of ON. 35 Similarly, Graham et al 36 reported a reduction of the temporal RNFL in 45 patients with RRMS without ON over 3 years.…”
Section: Discussionmentioning
confidence: 96%
“… 31 34 We have previously reported a lower RNFL thickness in patients with RRMS with and without a history of ON that was related to EDSS and MSSS. 28 Furthermore, a progressive thinning of RNFL has been shown in longitudinal studies of patients with MS, 35 37 and a recent longitudinal study of 57 patients with MS reported progressive RNFL thinning over 5 years, regardless of a history of ON. 35 Similarly, Graham et al 36 reported a reduction of the temporal RNFL in 45 patients with RRMS without ON over 3 years.…”
Section: Discussionmentioning
confidence: 96%
“…More interestingly, retinal Aβ plaques have been reported to be associated with brain pathology in AD patients, especially in the primary visual cortex [23]. In PD patients, Aβ deposits were also found in those with cognitive impairment [29]. We speculate that depositions of α-synuclein and Aβ are both involved in the pathogenesis of cognitive decline in PD.…”
Section: Discussionmentioning
confidence: 69%
“…Increased retinal nerve fiber layer (RNFL) thinning in adults with Down syndrome may represent early AD-related changes. Studies in other neurodegenerative diseases, such as multiple sclerosis and cognitive decline, have also suggested that a thinner RNFL may be a preclinical observation of dementia [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%